Succenturiate Lobe of Placenta: The Importance of Prenatal Diagnosis: Clinical Case - Villalobos-Rodríguez, Alejandro Lenin; Cárdenas-Núñez, Rafael del Carmen; Rodríguez-Villalobos, Paula; Padrón-Arredondo , Guillermo (British Journal of Healthcare and Medical Research, 2022)
Introduction. The succenturiate lobe is a morphological variation of the placenta that usually appears as a separate lobe from the main placental disc and can be single or multiple. This incidence increases when there is a history of pelvic infection, infertility, twin pregnancies, or preeclampsia. As for the product, it can present prematurity, growth disorder, and surgical resolution of pregnancy. Clinical case. Female, 30 years old, with the following obstetric history, menarche 15 years, rhythm 28X5 days, dysmenorrhea, IVSA: 15 years-old, Pregnancies 3, births one, 5 years-old, abortion one in the first trimester, cesarean section one. Emergency with detects blood pressure 154/90 mmhg, second take 166/93 mmhg. The diagnosis of pregnancy of 29.4 weeks of gestation by first-trimester ultrasound, preeclampsia is integrated. Among the surgical findings, a violaceous uterus is observed on the anterior and anterior sides, with clinical data of hematic infiltration secondary to placental abruption grade 1, Placenta with a succenturiate lobe Discussion. Placental anomalies are rare because they have a low incidence and in most cases, their diagnosis is made after delivery, however, they can cause problems in the third stage of labor such as placental retention or postpartum hemorrhage, the latter because the accessory vessels can rupture and compromise the viability of the product or during delivery, the accessory lobe can be retained causing hemorrhage and compromising the life of the mother. Conclusions: The antenatal diagnosis of placental anomalies is important because it allows these patients to be classified and considered as high-risk pregnancies.